Kenya : Sixth and Final Review Under the Three-Year Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Kenya's Sixth and Final Review Under the Three-Year Arrangement Under the Extended Credit Facility. Fiscal consolidation and the introduction of major reforms contributed to the program's success despite emerging challenges. All end-June 2013 quantitative targets were met. Net domestic assets and net foreign assets were comfortably within the program bounds. The authorities' primary fiscal balance outcome was in line with the program, and priority social expenditure was above the program's indicative target. The structural benchmark on auditing of compliance with value-added tax obligations by 50 large taxpayers before June 2013 was fulfilled. The IMF staff recommends completion of the review.